Hydrophobic starch acetate nanoparticles: A biopolymer-based system for sustained antitubercular drug release - Gaurang Rami; Pruthviraj Limbachiya; Mohyuddin Maradiya; Girish Acharya; Jabali Vora (Next Nanotechnology)
The objective of the research was to evaluate the utilization of starch acetate nanoparticles (SANPs) as drug delivery carriers for antitubercular drugs (Isoniazid, Rifampicin, and Pyrazinamide). The SANPs were synthesized employing ultrasonic-assisted double emulsification solvent evaporation method, permitting effective drug encapsulation. Chemical modification of native starch strengthened its hydrophobicity, as indicated by lower crystallinity in XRD analysis. The TGA validated the thermal stability of SANPs. Morphological investigation indicated a beehive-like structure with constant porosity changed to evenly dispersed spherical nanoparticles when Starch acetate is converted into SANPs. Dynamic light scattering measured the particle sizes of SANPs to be 161 nm. Drug encapsulation brought up the SANPs particle size to 249 nm. Isoniazid, Rifampicin, and Pyrazinamide exhibited 72 %, 83 %, and 75 % encapsulation efficiency at a 2:1 polymer-drug ratio, respectively. In phosphate-buffered saline (pH 7.4), drug release behavior exhibited 55 %, 30 %, and 45 % release of isoniazid, rifampicin, and pyrazinamide over 24 hours. The Korsmeyer-Peppas model demonstrated non-Fickian diffusion for all drug-encapsulated SANPs. Thus, these results contribute to the development of biopolymer-based drug delivery systems for sustainable release of antitubercular drugs.